Multimodal treatment of myophasal chronic pelvic pain in women: institutional experience - Reyes, Guadalupe Guerrero; Ochoa, Cristobal Barragan; Moysen Marin, Claudia M.; Ayala Quispe, Vianey B.; Del barco, Laura Escobar; González, Adrian Gutiérrez; Bailón, Aldo García; Velazquez, Ricardo Hernandez (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Chronic pelvic pain of myofascial origin is an underdiagnosed condition and with partial responses to the different treatment modalities. The objective of this study was to report the results of the multimodal management of Myofascial Chronic Pelvic Pain. Methods: Retrospective cohort of 33 patients with myofascial chronic pelvic pain, during the period 01 January 2016 to August 31, 2018, who were treated based on trigger point infiltration and analgesic vaginal electrostimulation. The analogous visual pain scale (VAS) was used at the beginning, sixth, twelfth and six months after the last electrostimulation session, in order to measure the effect of the treatment. Results: During the study period, 32 patients with chronic myofascial pelvic pain were found who received the multimodal scheme that is offered in our clinic. The average score of the EVA before starting the treatment was 8.5 points, at the sixth session of the treatment the average EVA was 3.6 points, at the twelfth session of 1.3 points and the average score of the EVA at six months after the last session of the multimodal treatment was 2.9 points. A significant difference was demonstrated in the average EVA score in the first with respect to the sixth, twelfth and six months (p = <0.000). There were no complications or adverse effects secondary to the multimodal treatment. Conclusions: Multimodal treatment was associated with progressive improvement in 80% of patients with miofascial chronic pelvic pain.